1980
DOI: 10.1111/j.1365-2125.1980.tb05845.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of propranolol and metoprolol to alter ventilatory responses to carbon dioxide and exercise.

Abstract: Neither propranolol (80 mg) nor metoprolol (100 mg) give orally to eight normal subjects altered mean ventilatory responses to carbon dioxide or to moderate graded exercise. Incremental doses of the drugs to totals of 320 mg propranolol and 400 mg metoprolol also did not effect these ventilatory responses. Both drugs markedly decreased the heart rate response to exercise. Neither propranolol nor metoprolol are likely to cause CO2 retention by an effect on the ventilatory responses to inhaled carbon dioxide or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
2

Year Published

1980
1980
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
8
2
Order By: Relevance
“…In our study the effects were seen most clearly with the cardioselective drug atenolol. The results with propranolol showed the same trend but with more scatter, possibly because of the much greater variation in plasma levels known to occur follow- Similarly small and frequent adjustments in exercise load were used in the negative study reported by Leitch et al (1980). Although Violante et al (1984) used only 25 watt increments they emphasize that their subjects were physically untrained unlike those of Pearson et al (1979).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…In our study the effects were seen most clearly with the cardioselective drug atenolol. The results with propranolol showed the same trend but with more scatter, possibly because of the much greater variation in plasma levels known to occur follow- Similarly small and frequent adjustments in exercise load were used in the negative study reported by Leitch et al (1980). Although Violante et al (1984) used only 25 watt increments they emphasize that their subjects were physically untrained unlike those of Pearson et al (1979).…”
Section: Discussioncontrasting
confidence: 40%
“…Enhanced hypoxic drive during exercise (Cunningham et al, 1968) may have as its basis increased sympathoadrenal activity. However, several studies have failed to demonstrate an effect on minute ventilation during graded exercise in normal subjects (Pearson, et al, 1979;Leitch et al, 1980;Petersen et al, 1983;O'Neill et al, 1984;McLeod et al, 1985) whereas others have shown reductions in minute ventilation after propranolol at submaximal levels of exercise (Twentyman et al, 1981;Violante et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent literature, a controversy exists as to whether f-blockade causes a blunting of the ventilatory response to carbon dioxide with publications supporting (Mustchin, Gribbin, Tattersfield & George, 1976;Patrick & Pearson, 1980) and opposing (Leitch, Hopkin, Ellis, Clarkson, Merchant & McHardy, 1980) this hypothesis. In exercise, fl-blockade has not been associated with an altered ventilatory response in the steady state (Pearson et al 1979;Leitch et al 1980;Conway, 1982), but it has been shown to lower ventilation at the onset ofexercise (Conway, 1982). The present results suggest an attenuation of ventilatory responses in very light exercise (0 W) due to fl-blockade, but less effect during 100 W exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, similar studies did not always show consistent results. For instance, all studies performed on healthy subjects who were able to reach high work rates (usually more than 200 W) showed a reduction of oxygen uptake and maximum work capacity after 3-adrenoceptor blockade (Pearson et al, 1979;Anderson et al, 1979;Twentyman et al, 1981;Tesch & Kaiser, 1983;Petersen et al, 1983), whereas no changes were found in studies carried out in subjects unable to reach such work levels, either healthy (Leitch et al, 1980) or suffering from mild hypertension (Fagard et al, 1980).…”
Section: Introductionmentioning
confidence: 99%